Problematika Persidangan Perkara Pidana di Masa Kahar - Siti Sahara; Nurasyiah Nurasyiah; Liza Agnesta Krisna (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2022)
This study is aimed at finding a model for the implementation of online criminal trial after the publication of SEMA Number 1 of 2020. This is an empirical legal research. Interviews were done with related parties to find models for the implementation of online trials and the obstacles faced by law enforcement institutions. Online criminal trials are meant to keep the defendants from the possible spread of COVID-19 in detention centers or prisons. However, the trials are legally weak. Data collection techniques include interviews and observations. The interviews were conducted using free guided techniques. The findings show that there are differences in the implementation of online criminal trials because the procedural law mechanism policy is very dependent on the ability of each institution. These constraints caused unfair trials, in other words, violate the principles of fair trial.